Fathering Patterns of Teenagers Towards Children with Stunting among the Bajo Tribe - Rismanudin Rismanudin; Muhammad Syahrul Alam; Wiwiek Hidayati Jaya; Wahyuni Hafid (Global Health Science Group, 2025)
Being a teenage father presents several challenges, including unpreparedness, shifting expectations, and uncertainty about the future. This study explores the life experiences of teenage fathers from the Bajo community who are raising children diagnosed with stunting. This study aims to understand how they navigate the complexities of early parenthood. This study adopts a qualitative approach using phenomenological methods. In a qualitative approach, the researcher acts as the main instrument of research. The study involved 12 participants, namely fathers of adolescents experiencing stunting. Data was collected through interviews and analyzed using Amadeo Georgie's data analysis method. Findings indicate that although many teenage fathers initially feel unprepared for their parental responsibilities, the desire to provide a better life for their children and families serves as a strong motivator. One of the most significant challenges is uncertainty about the future, particularly regarding financial stability and relationships with partners. Social support from family, community, and cultural traditions plays an important role in helping teenage fathers overcome these challenges. This support system not only offers emotional and financial assistance but also guidance in adapting to their new roles. Understanding the experiences of these teenage fathers is important for developing empowerment efforts and ensuring the well-being of fathers and children in the Bajo tribe.